Distinct features of rapidly progressive Alzheimer's disease. (20th December 2022) - Wang, Ping; Lynn, Audrey; Song, Yeunjoo E.; Haines, Jonathan L.
Abstract: Background: Rapidly progressive Alzheimer's disease (rpAD) has been recognized as a subtype of Late‐Onset Alzheimer's disease (LOAD) characterized by accelerated cognitive decline and/or reduced survival. The cause of variable progression rates of AD is largely unknown, and information regarding unique clinical features of rpAD is limited in longitudinal cohorts. Method: A retrospective analysis was performed on AD patients in the National Alzheimer's Coordinating Center (NACC) database from 2015 to 2021. Patients with rpAD were identified by reduced survival time (time from symptom onset to death < = three years) or accelerated cognition decline (defined as Mini‐Mental State Exam [MMSE] decrease > = 6 points/year or Clinical Dementia Rating scale [CDR] global score increase to 2 or 3 within three years). Demographic, clinical, and neuropsychological measurements were compared between patients with rpAD, typical "slow" progressive AD, and normal controls. rpAD patients and normal controls with Whole Genome Sequencing (WGS) data available from the Alzheimer's Disease Sequencing Project (ADSP) were selected for a pilot genome‐wide association study (GWAS). Result: Among 43, 746 NACC participants, 983 patients met our criteria for rpAD. rpAD patients had a mean survival of 2.8±0.5 years and their decline in MMSE was 6.4±5.9 points/year. Compared to controls, rpAD patients were older (72.6±8.6 vs 70.0±8.6, p < 0.001), more likely to be male (39% vs 33%, p < 0.001) and had fewer years of education (14.6±3.6 vs 15.9±3.0, p < 0.001). Compared to AD patients who progressed slowly, rpAD patients showed a more rapid decline in neuropsychological tests measuring working memory, language, attention, and executive function (p values < 0.001). GWAS was performed on 175 rpAD patients and 525 age‐ and sex‐matched NACC controls. 49 genetic variants showed significant associations with rpAD (p‐values < 1 × 10 −5 ). Conclusion: In the longitudinal NACC cohort, rapidly progressive AD constitutes an important subset, featuring a short survival with rapid decline of cognitive and neuropsychological functions. Previously known genetic risk variants for AD were not found in this rpAD cohort. Further examination of rpAD cohort could help identify unique mechanisms that drive the rate progression in AD for different groups of patients.